2019
DOI: 10.15761/crt.1000273
|View full text |Cite
|
Sign up to set email alerts
|

Long-term (10-year) efficacy of finasteride in 523 Japanese men with androgenetic alopecia

Abstract: Finasteride is a standard medical treatment for androgenetic alopecia; however, no long-term study of up to 10 years has been performed in Japan. Therefore, we evaluated the efficacy and safety of 1 mg/day finasteride in 532 Japanese men who were treated for androgenetic alopecia for 10 years. We performed subjective evaluations, using questionnaires administered to patients, in addition to the objective evaluation by doctors. The efficacy was assessed using the Norwood-Hamilton scale and modified global photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…The clinical efficacy of oral finasteride for treating AGA is well established. Long‐term studies of oral finasteride 1 mg in men with AGA demonstrated slower progression of hair loss or enhanced hair growth, compared with baseline and/or placebo, as early as 3 months after starting the treatment and extending for 5–10 years 6−10 . Although oral finasteride is generally well tolerated, 5 in some patients 5α‐reductase inhibition is associated with sexual adverse effects (erectile dysfunction, ejaculation problems, decreased libido), 11 and increased risk of depression, 12 prompting health authorities in some countries to include warnings in the product labelling 13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical efficacy of oral finasteride for treating AGA is well established. Long‐term studies of oral finasteride 1 mg in men with AGA demonstrated slower progression of hair loss or enhanced hair growth, compared with baseline and/or placebo, as early as 3 months after starting the treatment and extending for 5–10 years 6−10 . Although oral finasteride is generally well tolerated, 5 in some patients 5α‐reductase inhibition is associated with sexual adverse effects (erectile dysfunction, ejaculation problems, decreased libido), 11 and increased risk of depression, 12 prompting health authorities in some countries to include warnings in the product labelling 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Long‐term studies of oral finasteride 1 mg in men with AGA demonstrated slower progression of hair loss or enhanced hair growth, compared with baseline and/or placebo, as early as 3 months after starting the treatment and extending for 5–10 years. 6 , 7 , 8 , 9 , 10 Although oral finasteride is generally well tolerated, 5 in some patients 5α‐reductase inhibition is associated with sexual adverse effects (erectile dysfunction, ejaculation problems, decreased libido), 11 and increased risk of depression, 12 prompting health authorities in some countries to include warnings in the product labelling. 13 Topical administration of finasteride offers the potential to reduce systemic effects related to its mechanism of action by preferentially inhibiting 5‐α reductase in the scalp, as has been suggested in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of 399 patients, dutasteride blocked 98.4 ± 1.2% of DHT at 5 mg/d dose compared to 70.8 ± 18.3% with the same finasteride dose 32 . The long‐term safety of finasteride, over a period of 10 years has been documented in studies 33,34 . Recent reports about postfinasteride syndrome have created a fear among patients seeking treatment.…”
Section: Safety Profilementioning
confidence: 99%
“…6 The third investigation, "Long-Term (10-Year) Efficacy of Finasteride in 523 Japanese Men with Androgenetic Alopecia," was evaluated from December 2005 to January 2009. 5 The same patients were included in the three investigations, but each study period was completely different. In two of the investigations, adverse reactions were assessed through self-reported evaluations by patients.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3] Although finasteride has been globally used for more than 20 years, only a few investigations for up to 10 years have been demonstrated worldwide. 4,5 The authors have previously demonstrated three investigations of efficacy and safety of large-scale and long-term AGA treatment with finasteride (3,177 cases in 2.5 years, 801 cases in 5 years, and 532 cases in 10 years, respectively). [5][6][7] The objective of this article is to summarize the three investigations, and to consider them as a base for future studies over the next 20 to 30 years or more.…”
Section: Introductionmentioning
confidence: 99%